2014
DOI: 10.1007/s11657-014-0178-z
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of low vitamin D status in adolescent females in Kuwait: implications for high peak bone mass attainment

Abstract: Low vitamin D status is prevalent in Kuwaiti adolescent females, which may have a negative impact on their bone mineralization and accrual. Further investigation is needed to reveal the underlying causes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 40 publications
1
22
1
Order By: Relevance
“…Invitation letters were sent to the mothers of students from a previous study38 who were recruited from schools located in each governorate in Kuwait. In addition, female students in the College of Basic Education, Public Authority for Applied Education and Training, Kuwait were also invited to participate.…”
Section: Methodsmentioning
confidence: 99%
“…Invitation letters were sent to the mothers of students from a previous study38 who were recruited from schools located in each governorate in Kuwait. In addition, female students in the College of Basic Education, Public Authority for Applied Education and Training, Kuwait were also invited to participate.…”
Section: Methodsmentioning
confidence: 99%
“…21, 22, 23, 24, 25, 26 For example, a Kuwaiti and an Emirati study reported that ~98 and 83% (respectively) of the participants had serum 25(OH)D less than 20 ng ml −1 . 24, 25 Studies thus far conducted in Qatar on vitamin D were specific to a certain population (elderly and health professionals). At the same time, the prevalence of MetS was measured to be ~26.5%, according to the International Diabetes Federation (IDF) criteria, amongst Qataris aged 20 and over.…”
Section: Introductionmentioning
confidence: 99%
“…While Kuwait is blessed with ambient sunshine all over the year, it is possible that the lifestyle and the harsh hot weather during the long summer discourage daily exposure to the sun, needed to maintain adequate vitamin D levels and bone quality. Approximately 86% of Kuwaiti females were reported to show hypovitaminosis D,26 and up to 60% of neonates had undetectably low vitamin D levels at delivery 27…”
Section: Discussionmentioning
confidence: 99%